Sustainability-Based Smart Cloud Accounting Model for MSME Financing Access in Kendari City - Sahlan, Fahmi; Hidayat, Muhammad Fery; Pracita, Sriayu (Amkop Management Accounting Review (AMAR), 2025)
This study aims to develop and validate a conceptual framework for a sustainability-based (ESG) bright cloud accounting model to address information gaps and improve access to financing for manufacturing MSMEs in Kendari City. The research method used is Research and Development (R&D) following the Borg & Gall model, involving problem identification, needs validation, model design, and expert validation. Data were collected through surveys and in-depth interviews with 30 MSMEs and 30 experts (academics, practitioners, and bankers). The research successfully designed a model framework consisting of four integrated components: an automated financial recording system, quantified ESG indicators, financial and ESG analysis engines, and comprehensive reporting outputs. Expert validation indicated a very high feasibility of the model, with average scores of 4.4 for the framework and 4.6 for the indicators, as well as the highest relevance (score 4.7) for the needs of green financing assessment by banks. The key conclusion is that this model has the potential to be an effective solution for reducing information asymmetry, documenting sustainability practices, and serving as a credible signaling tool for MSMEs in accessing financing, in line with sustainable finance regulations in Indonesia.